Earnings Inequality in International Perspective - Franco Peracchi (Luxembourg Income Study (LIS), 1999)
The increase in dispersion of personal earnings in the USA has received considerable attention and has been analyzed extensively. The evidence for other countries is less systematic. There are a few comparative studies, but they tend to focus on descriptions of the overall distribution of income or earnings. This paper compares the USA with other countries in order to understand whether the US experience is relatively unique or is instead part of a global (or perhaps industrial countries) phenomenon. The paper is mainly descriptive and relies on the empirical evidence from the micro-data of the Luxembourg Income Study (LIS), spanning a period of about twenty years from the mid 1970s to the mid 1990s. It focuses on personal earnings, as opposed to personal or household income, and looks at two main determinants of the changes in the distribution of earnings at the aggregate level, namely changes in between-group and within-group dispersion, as well as the relationship between changes in relative wages and in relative employment. Grouping of the population is based on gender, age and educational attainments. Our main empirical finding is that most of the stylized facts known to hold for the USA also hold for a large majority of the countries included in the LIS database. Therefore, far from being unique, the US experience appears to be part of a phenomenon that is common to many developed countries.
Keywords: 330; Einkommensverteilung; Vergleich; USA; Industrieländer